2009
DOI: 10.1016/j.juro.2009.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Early Detection Program Recruitment Methods and Show Rates in Men at High Risk

Abstract: Purpose-Men with a family history (FH) of prostate cancer (PCA) and African American (AA) men are at higher risk for PCA. Recruitment and retention of these high-risk men into early detection programs has been challenging. We report a comprehensive analysis on recruitment methods, show rates, and participant factors from the Prostate Cancer Risk Assessment Program (PRAP), which is a prospective, longitudinal PCA screening study.Materials and Methods-Men 35-69 years are eligible if they have a FH of PCA, are AA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…This is consistent with the observations of Weinrich, Boyd, Bradford, Mossa, and Weinrich (1998) and Powell et al (1997) who observed that recruitment of AA men, educational assessment, and PCa screening were most successful when conducted simultaneously at natural gathering places such as work and church sites. Giri et al (2009) previously reported that the “show rate” for evaluation was adversely affected by AA race, lower education level, not being married/partnered, being unemployed, lower income, and having no family history of PCa while using a model which separated initial recruitment from evaluation. Similar adverse risk factors were common to the POP population.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the observations of Weinrich, Boyd, Bradford, Mossa, and Weinrich (1998) and Powell et al (1997) who observed that recruitment of AA men, educational assessment, and PCa screening were most successful when conducted simultaneously at natural gathering places such as work and church sites. Giri et al (2009) previously reported that the “show rate” for evaluation was adversely affected by AA race, lower education level, not being married/partnered, being unemployed, lower income, and having no family history of PCa while using a model which separated initial recruitment from evaluation. Similar adverse risk factors were common to the POP population.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies examining the impact of men at risk of prostate cancer and the associated recruitment and retention into early detection programs have shown that these programs are becoming more prevalent (10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…The design of the Prostate Cancer Risk Assessment Program has been described previously 16, 17. Briefly, the Prostate Cancer Risk Assessment Program was established in 1996 with the objectives of providing prostate cancer education, risk assessment, and early detection for men at high risk and to research genetic and epidemiologic factors contributing to the increased susceptibility to prostate cancer.…”
Section: Methodsmentioning
confidence: 99%
“…Eligibility criteria include men aged 35 to 69 years with any of the following: 1) 1 first‐degree relative with prostate cancer, 2) 2 second‐degree relatives with prostate cancer on the same side of the family, 3) any African American man regardless of a family history of prostate cancer, or 4) men with known mutations in BRCA1 or BRCA2 . Recruitment of Prostate Cancer Risk Assessment Program participants has been reported in detail16 and includes physician referrals, radio advertisements in the greater Philadelphia area, referrals by family/friends, and community events/health fairs. In addition to Fox Chase Cancer Center, participants are currently also recruited at 2 community Fox Chase Cancer Center Partner hospitals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation